Effect of Thermal Environment on the Mechanical Behaviors of Building Marble - Haijian Su; Hongwen Jing; Qian Yin; Liyuan Yu (Advances in Civil Engineering)
High temperature and thermal environment can influence the mechanical properties of building materials worked in the civil engineering, for example, concrete, building rock, and steel. This paper examines standard cylindrical building marble specimens (Φ50 × 100 mm) that were treated with high temperatures in two different thermal environments: vacuum (VE) and airiness (AE). Uniaxial compression tests were also carried out on those specimens after heat treatment to study the effect that the thermal environment has on mechanical behaviors. With an increase in temperature, the mechanical behavior of marble in this study indicates a critical temperature of 600°C. Both the peak stress and elasticity modulus were larger for the VE than they were for the AE. The thermal environment has an obvious influence on the mechanical properties, especially at temperatures of 450∼750°C. The failure mode of marble specimens under uniaxial compression is mainly affected by the thermal environment at 600°C.